Un framework para la gestión de la memoria organizacional orientado a proyectos de investigación dentro de una institución de educación superior - Corro Portella, Linder Maycol (2015)
An institution of higher education that develops research projects can learn and remember the knowledge generated by these projects. In this applied research proposes a framework for the management of organizational memory oriented research projects within a Higher Education Institution to support the capture, storage and retrieval of knowledge from research projects, which could provide access to documents or documentation thereof, of the events that accompany them and are specific for each research project, the sources of information necessary to conduct a research project, the skills required for a given (s) project (s) for research and solutions or results of research projects.